A Moving Grove: Our Climate Future and Its Branching Possibilities. (6th July 2022) - de Monchaux, Nicholas
Abstract: MIT Professor and Head of Architecture there, Nicholas de Monchaux explores the recent forays of Bartlett School of Architecture professors Mark Smout and Laura Allen into forestry, regreening and ecology, for example their 'Rescue Lines' drawing/table project, conceived in conjunction with LA‐based critic Geoff Manaugh and presented at the Venice Architecture Biennale in 2021. De Monchaux's wide‐ranging exposition offers further thoughts on the nature of drawing relative to Smout Allen's work, with reference to the underwater forest made by the timber piles below Venice.